Outcomes after hospitalisation with spontaneous bacterial peritonitis over a 13-year period: a retrospective cohort study. Issue 4 (6th April 2023) - Ubhi, Nicholas; Mourad, Adele; Tausan, Matija; Lewis, Declan; Smethurst, James; Wenlock, Rhys; Gouda, Mahmoud; Bremner, Stephen; Verma, Sumita
Abstract : Goals: Assess outcomes in patients with an index presentation of spontaneous bacterial peritonitis (SBP) over a 13-year period. Background: SBP, a bacterial infection of ascites, has a poor prognosis. Study: Retrospective cohort study assessing mortality (standardised to 32 months) and prognostic factors in patients with SBP during two periods: period 1 (June 2006–November 2012) and period 2 (December 2012–May 2019). Results: The study included 178 patients who were followed up for 11.6 (29.2) months. Mortality was high, with 12-, 24- and 32-month survival being 32%, 26% and 24%, respectively. Inpatient mortality was 36% with mortality in those surviving hospitalisation being 62%. Serum creatinine at the time of SBP diagnosis was an independent predictor of mortality at 32 months [hazard ratio (HR) 1.002, P  = 0.023] and inpatient mortality (HR 1.003, P  = 0.035). Positive ascitic fluid culture and ascitic fluid neutrophil count were independent predictors of 32-month (HR 1.679, P  = 0.008) and inpatient mortality (HR 1.0001, P  = 0.005), respectively. Patients in period 2 had lower ascitic fluid albumin (5.9 ± 3.3 g/L vs. 10.8 ± 5.4 g/L, P  < 0.001), higher ascitic fluid neutrophil count (815.0 cells/mm 3 vs. 345.0 cells/mm 3, P  < 0.001) and higher rates of hepatorenal syndrome-acute kidney injury (58 vs. 35%, P  = 0.002). Mortality at 32 months and mortality in those surviving hospitalisation were similar at 78 vs. 73%, P  = 0.392 and 66 vs. 58%, P  = 0.355, for periods 1 and 2, respectively. Conclusions: Despite more advanced initial presentations, mortality rates have remained similar over the last 13 years. Serum creatinine at the time of SBP diagnosis is an independent predictor of mortality.